Typing of 111 ancestry informative markers in an Albanian population. (December 2015) - Ribeiro, J.; Pereira, V.; Kondili, A.; Miniati, P.; Børsting, C.; Morling, N.; ,
Abstract: Genetically based prediction of ancestry has a great potential in forensic genetics and may be used as an investigative lead in crime case work or missing person identification. The EUROFORGEN-NoE consortium developed four PCR and SBE multiplexes for typing of 111 ancestry informative markers (AIMs) with the purpose of differentiating Middle Eastern populations from those of the rest of the world (publication in preparation). Before these multiplexes can be applied in forensic case work, population data for these markers are needed. In this work, samples from 51 Albanian individuals were typed with the AIMs set and, at the same time, the performance of each SNP assay was evaluated. After PCR and SBE, samples were typed using the Sequenom MassARRAY ® . All samples were typed at least two times. The mass spectra were analyzed using Typer 4 and the genotype calls were further analyzed with a custom designed script in the software R. The results were compared to other population samples previously typed for the same markers. The panel of AIMs was capable of differentiating the Albanian population from other population groups except for the Greek population. These results were expected due to the history and the geographical proximity of Albania and Greece.